2018
DOI: 10.1007/s00406-018-0878-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and electrophysiological responses to fairness norm violations in antisocial offenders

Abstract: Antisocial personality disorder is characterized by a stable, lifelong pattern of disregard for and violation of others' rights. Disruptions in the representation of fairness norms may represent a key mechanism in the development and maintenance of this disorder. Here, we investigated fairness norm considerations and reactions to their violations. To examine electrophysiological correlates, we assessed the medial frontal negativity (MFN), an event-related potential previously linked to violations of social exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 56 publications
2
15
0
2
Order By: Relevance
“…These results support the hypothesis that in UG the MFN amplitude of Responders is likely to be associated with the expectation of fairness on the part of the Proposers. Thus, the perception of the offers by the Responders —all participants of this study played the role of Responders— depended on the behavioral group, and not on the absolute value of the endowment share [47,52,114,125].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results support the hypothesis that in UG the MFN amplitude of Responders is likely to be associated with the expectation of fairness on the part of the Proposers. Thus, the perception of the offers by the Responders —all participants of this study played the role of Responders— depended on the behavioral group, and not on the absolute value of the endowment share [47,52,114,125].…”
Section: Discussionmentioning
confidence: 99%
“…The MFN is a wave component that has been observed in association with some assessment of fairness [44][45][46][47], social status and altruistic bias [40,51,52,114], but only one study has reported quantitative ERP results in Allocators during DG [47]. However, these studies did not clearly distinguish between behavioral groups.…”
Section: Medial Frontal Negativitymentioning
confidence: 99%
See 1 more Smart Citation
“…结果 发现, 个体并不是按照利益最大化的理性原则提出分 配方案, 提议者往往会将一半左右的金额分配给对方, 而响应者通常会拒绝少于总金额中20%的提议 [9,13] . 进 一步研究发现, 响应者的公平决策受到社会情境的影 响, 如个体明确知道自己在与电脑进行博弈时, 对不公 平 提 议 的 拒 绝 率 显 著 低 于 与 真 实 人 类 进 行 的 博 弈 [11,14,15] . 因此, 研究者认为, 在UG中响应者拒绝不公 平提议反映了个体在社会决策情境下的公平偏好.…”
Section: 不患寡而患不均 公平感是影响对他人社会认知unclassified
“…使用高时间分辨率的事件相关电位技术(event-related potential, ERP)研究UG任务中大脑对不同提议类 型的时间进程, 发现反馈相关负波(feedback-related negativity, FRN)和P300成分反映了个体对提议公平性的 不同评价阶段 [14,16,17] . [18,22] .…”
Section: 不患寡而患不均 公平感是影响对他人社会认知unclassified